The Influence Of Self-Motivation And Entrepreneurship Learning On Students' Interest In Shari'ah Banking Study Program For Entrepreneurship - Adinda Putri; Dian Meliza; Fitrianto Fitrianto (Denisya Smart Consulting, 2023)
The aim of this study is to determine the influence of self-motivation and learning in entrepreneurship courses on students' interest in the Shariah banking entrepreneurship program. The population in this research is students who have taken entrepreneurship courses. A sample of 47 respondents was used for this research. Data collection was done through observation, interviews, questionnaires and documentation measured using a Likert scale. Data analysis was carried out using the multiple linear regression method with the help of SPSS software. The results of this research show that self-motivation has a significant influence on students' interest in entrepreneurship with a significant value of 0.015 <0.05. Entrepreneurship learning has a significant influence on students' interest in entrepreneurship with a significant value of 0.000 < 0.05. Self-motivation and entrepreneurship learning simultaneously influence interest in entrepreneurship among students in the Sharia Banking Study Program. This is shown by the value Fcount > Ftable, namely with a significant value of 11.579 > 3.21